Herpes Simplex virus type 2 seroprevalence and risk factors among adolescents and youth with HIV-1 in Northern, Tanzania - Rashid Madebe; Ireen Kiwelu; Arnold Ndaro; Filbert Francis; Vito Baraka; Zahra Theilgaard; Terese Katzenstein (Journal of Infection in Developing Countries)
Introduction: Herpes Simplex virus type 2 (HSV-2) infection is associated with an increased risk of human immunodeficiency virus type 1 (HIV-1) acquisition and transmission. Individuals co-infected with HIV-1 and HSV-2 may have longer lasting, more frequent and severe outbreaks of herpes symptoms. Previous studies have assessed HSV-2 seroprevalence and associated risk factors in adult populations. However, there is limited data on the HSV-2 seroprevalence among adolescents and youth living with HIV-1. The study aimed to determine the HSV-2 seroprevalence and associated risk factors among adolescents and youth living with HIV-1 at referral hospital setting in Northern Tanzania.